2011
DOI: 10.1186/1742-2094-8-79
|View full text |Cite
|
Sign up to set email alerts
|

Microglial p38α MAPK is a key regulator of proinflammatory cytokine up-regulation induced by toll-like receptor (TLR) ligands or beta-amyloid (Aβ)

Abstract: BackgroundOverproduction of proinflammatory cytokines from activated microglia has been implicated as an important contributor to pathophysiology progression in both acute and chronic neurodegenerative diseases. Therefore, it is critical to elucidate intracellular signaling pathways that are significant contributors to cytokine overproduction in microglia exposed to specific stressors, especially pathways amenable to drug interventions. The serine/threonine protein kinase p38α MAPK is a key enzyme in the paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
193
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(208 citation statements)
references
References 57 publications
(61 reference statements)
8
193
2
Order By: Relevance
“…Further supporting the role of MK2 in microglial inflammation, Bachstetter et al (2011) demonstrated that antineuroinflammatory efficacy of the p38 MAPK inhibitor MW01-2-069A-SRM is associated with decreased phosphorylation state of MK2. Similarly, in primary neuron-glia cocultures, the dopaminergic neurons from MK2-deficient mice were significantly more resistant to LPS-induced neurotoxicity compared with cells from wild-type mice.…”
Section: The Role Of Mk2 In Neuroinflammationmentioning
confidence: 92%
“…Further supporting the role of MK2 in microglial inflammation, Bachstetter et al (2011) demonstrated that antineuroinflammatory efficacy of the p38 MAPK inhibitor MW01-2-069A-SRM is associated with decreased phosphorylation state of MK2. Similarly, in primary neuron-glia cocultures, the dopaminergic neurons from MK2-deficient mice were significantly more resistant to LPS-induced neurotoxicity compared with cells from wild-type mice.…”
Section: The Role Of Mk2 In Neuroinflammationmentioning
confidence: 92%
“…p38 MAPK, which responds to inflammatory and oxidative stress, is activated in the AD brain (14,15), and mediates A␤-induced inflammatory activation in cultured microglia (21). Studies have suggested that inhibition of p38␣ MAPK retards AD pathogenesis; for example, oral administration of p38␣ MAPK inhibitor successfully reduced neuroinflammation and synaptic dysfunction in APP-transgenic mice (22,46).…”
Section: Discussionmentioning
confidence: 99%
“…A␤ and glutamate have each been shown to activate p38 MAPK in cultured neurons by increasing reactive oxygen species (16,17), and the A␤-triggered microglial release of inflammatory mediators, especially IL-1␤, is hypothesized to activate neuronal p38 MAPK (18 -20). p38␣ MAPK mediates A␤-initiated microglial inflammatory activation (21,22), phosphorylates Tau protein in neurons (20,23,24), and mediates A␤-induced synaptic impairment in the cultured hippocampal slice (25). However, no experiments have yet elucidated whether p38 MAPK phosphorylates BACE1 and regulates A␤ generation.…”
mentioning
confidence: 99%
“…These cells cluster together and exhibit a deramified and hypertrophic morphology. Morphological changes following diffuse injury in mice ( Mus musculus ) are dependent on intact p38α MAPK signaling, a pathway that also prompts microglial pro-inflammatory cytokine production [39]. Diffuse brain injury results in transiently elevated IL-1β, TNFα, and CD14 in the cortex and hippocampus of mice as early as 4 hours after injury, which returns to baseline by 72 hours [40].…”
Section: Acute Activation Of Microglia After Tbimentioning
confidence: 99%